Processing Steps exhibit panels (circa 1950) - Hercules Incorporated (1950)
Two photographs of exhibit panels depicting steps in the processing, manufacture, and packaging of explosives sold by the Hercules Powder Company. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Hercules Incorporated; Chemical industry; Corporations; Explosives; Explosives industry; Advertising; Advertising, Industrial